Diagnostic yield of dental radiography and digital tomosynthesis for the identification of anatomic structures in dogs - May, Tanner; Lommer, Milinda Jean; Arzi, Boaz; Goldschmidt, Stephanie Lynne; Hatcher, David C.; Soltero-Rivera, Maria M. (Frontiers in Veterinary Science, 2024)
IntroductionThe purpose of this study was to evaluate the use of a novel imaging modality, digital tomosynthesis (DT), for identification of predefined anatomic dental and maxillomandibular structures in dogs.MethodsDT images were compared to conventional intraoral dental radiography (DR) for the diagnostic yield regarding the presence and quality of visualization of 35 structures. DT imaging and full mouth DR were obtained on 16 canine cadaver heads and a semi-quantitative scoring system was used to characterize the ability of each imaging method to identify the anatomic structures.ResultsThe results demonstrated that each imaging modality, and orientation, was superior for certain anatomic structures.DiscussionOverall, although one modality did not prove superior to the other, digital tomosynthesis appears to be an appropriate novel tool for identification of specific anatomic structures in the dog skull.